The Urgency of Transdisciplinary Approaches in Contemporary Islamic Law Studies - Asni, Asni; L. Diab, Ashadi; Kartini, Kartini; Kamarudddin, Kamarudddin (KnE Social Sciences, 2022)
Islamic law studies have encountered several contemporary issues. Islamic law is expected to contribute toward current problems faced by modern society. Therefore, ideally, studies of Islamic law should be developed through a transdisciplinary approach. This should be carried out through the theocentric paradigm integration framework and anthropocentric Islamic law. It is known that Islamic law initially came from the revelation (Qur’an and hadith), and that it aims for the benefit of humans. In its construction, Islamic law enforces the foundation of the principle of Tauhid and is developed through humanism principles such as humanity, fairness, equality and tolerance. From this perspective, the transdisciplinary approach should be taken into account in the studies of Islamic law. This paper elaborates on the development of contemporary Islamic law studies through a transdisciplinary approach from the perspective of formal and material objects. The results affirmed that contemporary Islamic law studies need to combine normative and empirical approaches, and textual and contextual analysis based on maqasid al-syariah. To be relevant to the needs of people and social issues, Islamic law should be integrated with other sciences. Only with this method can Islamic law help to effectively and comprehensively solve social problems and become a law that is rahmatan lilalamin. Keywords: transdisciplinary approach, Islamic law, normative-empirical, holistic, Maqasid al-Syariah